Managing archaeological collections in Middle Eastern countries : a good practice guide - Fitzpatrick, Dianne (Archaeopress archaeology., 2016)
In this guide, archaeologist Dianne Fitzpatrick sees archaeological collections management as a means of integrating achievable good-practice strategies into research designs and site management plans from the outset.